2014
DOI: 10.1186/1471-2407-14-587
|View full text |Cite
|
Sign up to set email alerts
|

Rab11 regulates E-cadherin expression and induces cell transformation in colorectal carcinoma

Abstract: BackgroundIn the process of epithelial mesenchymal transition EMT, the disassembly of junctional adhesion complexes such as E-cadherin is a remarkable sign during changes in cell morphology and polarity. However, E-cadherin expression is dynamic, and is regulated by the cellular endocytic system; it is also involved in cell signaling mechanisms. In this study, we investigated the role of E-cadherin in colorectal tumors and the relationship with recycling endosome protein Rab11 in colon cell transformation.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
(36 reference statements)
3
27
0
Order By: Relevance
“…We observed that aggregates with the highest frequency of collective invasion had elevated levels of both mesenchymal and epithelial markers, and that E-cadherin in particular promoted collective invasion, which suggests an additional role for EMT markers in the cellular response to physical cues such as IFP. These results are consistent with those from other studies showing that E-cadherin expression may actually enhance metastatic potential, 34, 39, 40 which contrasts with the classical view of E-cadherin as a tumor suppressor. 4145 Remarkably, we found that E-cadherin was enriched in invading cohorts.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that aggregates with the highest frequency of collective invasion had elevated levels of both mesenchymal and epithelial markers, and that E-cadherin in particular promoted collective invasion, which suggests an additional role for EMT markers in the cellular response to physical cues such as IFP. These results are consistent with those from other studies showing that E-cadherin expression may actually enhance metastatic potential, 34, 39, 40 which contrasts with the classical view of E-cadherin as a tumor suppressor. 4145 Remarkably, we found that E-cadherin was enriched in invading cohorts.…”
Section: Discussionsupporting
confidence: 92%
“…Cadherin‐based junctions between cells that maintain ‘supra cellular’ properties, such as collective polarization and force generation, have been claimed to characterize collective cell migration . Our histological study demonstrated dual overexpression of E‐cadherin and Rab11 in most carcinoma tissues with amorphous mass morphologies, and expression of both of these proteins in tumour nests has also been observed previously . These histological phenotypes have also previously been described in collective cell migration .…”
Section: Discussionsupporting
confidence: 87%
“…Solitary overexpression of Rab11 was found in 26 patients (23·0%), and solitary overexpression of E‐cadherin was found in 10 patients (8·9%). Only three patients (2·7%) lacked any overexpression of Rab11 and E‐cadherin . In the present study, the survival of the patients was further analysed, and the dual expression of the Rab11 and E‐cadherin was correlated with poor prognosis in CRC.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations